Die Anwendbarkeit privatrechtlicher Vorschriften im Verwaltungsrecht Dargestellt anhand der privatrechtlichen Regeln über Rechtsgeschäfte und anhand des Allgemeinen Schuldrechts - Wall, Heinrich de (Mohr Siebeck, 1999)
The Applicability of Civil Law Regulations in Administrative Law. The Principles of Civil Law regarding Legal Transactions and the General Law of Obligations. By Heinrich de Wall.
PublicationDate: 20200518
Keywords: Verwaltungsrecht -- Bürgerliches Recht -- Array